Navigating Racial Identity: Denial, Repression, and Resilience in Novel Caucasia by Danzy Senna - Dani , Ammar; Iman, Diah Tyahaya (LingoLitera, 2026)
This study examines Racial Identity, Denial, Repression and Resilience in Danzy Senna's Caucasia. This research identifies how the author depicts Birdie's racial identity development, defense mechanisms, and resilience in responding to social expectations. This study employs a descriptive qualitative method, applying Sigmund Freud's "Model of Psyche" and defense mechanisms (Denial and Repression), as well as Emmy Werner's resilience theory, which encompasses three stages: trauma identification, adaptive analysis, and positive transformation. Data are collected from the novel and relevant literature. The results show that Birdie's racial identity develops through internal conflict, balancing id, ego, and superego. Trauma and social pressures affect her resilience development, which is rooted in the dissonance between her authentic self and societal expectations. The study demonstrates how Birdie employs defense mechanisms to cope with racial identity and social expectations. Her journey reflects the psychological struggle of biracial individuals seeking acceptance in racially divided societies.